Socialization of tribal girls into soccer: identifying the potential socializing contexts - Awashes Subba; Viswanath Sundar; Kuntal Karmakar (CV. Literasi Indonesia, 2026)
This qualitative study investigates the complex, multi-level socializing contexts that shape marginalised tribal girls' trajectories toward becoming professional soccer players. Utilizing a grounded theory methodology, in-depth interviews were conducted with 13 female athletes from the Santhali tribe in West Bengal, India. Data were evaluated through thematic analysis employing constant comparative coding. Grounded in a socio-ecological framework underpinned by interactionist and internalisation paradigms, the research identifies four pivotal socializing contexts: interpersonal, cultural, institutional, and mass media. Findings reveal that the interpersonal context serves as the paramount catalyst for sports socialization. Diverging from traditional, club-based, and parent-centric models of sports socialization, this study highlights the unique roles of mothers, elder siblings, neighbourhood peers, and local retired coaches. These specific actors formed an informal network that facilitated opportunities, financial and emotional support, and the substitution of household work responsibility. Furthermore, the girls’ sporting ambitions were reinforced by village subcultures, their self-perceived physicality, and the aspirational influence of televised sports celebrities. While situated within a specific tribal group, which limits broad generalisability, this qualitative study offers theoretical insights and illustrates that sports socialization and gendered athletic behaviours do not occur in a vacuum; instead, they are deeply embedded within complex, multi-layered social contexts that actively shape, and are shaped by, the deliberate negotiation and choices of young women navigating their way into the sporting world.